تعليم مهارة الكلام باستخدام الوسائط المتعددة للدارسين الناطقين بغير العربية في المستوى المتوسط - Nur Arifah binti Samat (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study deals with the topic of teaching Arabic speaking skills to non-Arabic learners at the intermediate level in Islamic Revealed Knowledge courses who are learning the Arabic language at the Quranic Language Division, Centre for Foundation Studies, International Islamic University Malaysia. The study aims to identify the problems in teaching speaking skills to non-native Arabic speakers. It also intends to explore their perceptions on the use of multimedia in teaching speaking skills. This study is a quantitative study and was conducted on 60 students using a questionnaire. Based on the views and suggestions from these students, a multimedia learning programme was designed by using Microsoft PowerPoint (MS PPT) based on ADDIE instructional design model. After that, the multimedia learning program was implemented on 35 other students and a second questionnaire was distributed to them in order to identify the level of acceptance on the use of this multimedia programme in improving their Arabic speaking skills based on its performance and language content. This study discovered that 95% of the students had a positive view on the use of multimedia application in their learning process and 86.67% of them believe that this multimedia programme could assist them to master Arabic speaking skills. The findings confirmed that the use of computers in teaching and learning process has become an urgent and necessary need.